ЎЗБЕКИСТОН ҲУДУДИДА ГАНЧКОРЛИК САНЪАТИ ТАРИХИЙ РИВОЖЛАНИШ БОСҚИЧЛАРИНИНГ ИЛМИЙ АСОСЛАРИ (Scientific journal of the Fergana State University, 2023)
This article covers the processes of the development of the history of Central Asian art of “ganch”. Information about carving schools, as well as about the types of patterns and masters is given